Pengaruh Penerapan Program Tilawah Terhadap Peningkatan Kefasihan Membaca Al-Qur'an Di MAS PAB 2 Helvetia - Bella Tandy; Junaidi Junaidi (LPPM Universitas Labuhanbatu, 2026)
The purposive sampling method is a sampling technique with certain considerations, the purpose of this study was to determine the effect of implementing the recitation program on increasing fluency in reading the Qur'an at MAS PAB 2 Helvetia. The population in this study was class X MAS PAB 2 Helvetia which consisted of two classes, namely MIA and IIS. In this purposive sampling technique, a sample of 30 people was obtained from 2 classes with a total number of 13 men and 17 women, the data analysis technique used in this study was hypothesis testing, while the results of this study were shows that there is an effect of implementing the recitation program on increasing fluency in reading the Qur'an in MAS PAB 2 Helvetia, this study accepts the hypothesis that the high effect of implementing the recitation program on increasing fluency in reading the Qur'an in MAS PAB 2 Helvetia.